Assessment of the potential of combining wave and solar energy resources to power supply worldwide offshore oil and gas platforms. (1st November 2020) - Oliveira-Pinto, Sara; Rosa-Santos, Paulo; Taveira-Pinto, Francisco
Highlights: Method to define best combination of power production from wave and solar energies. Combination of both resources reduces intermittency and intra-annual variability. Results show an increase in capacity factors up to 24% for the combined system. Levelized cost of energy estimated ranged from 131 €/MW to 263 €/MWh. Reductions in emissions estimated at 281, 915 ton/year at each case study site. Abstract: Offshore oil and gas platforms have very high-power demands that are usually met locally by using gas turbines. Nowadays, the industry is seeking for environmentally friendly alternatives to power supply those facilities, such as by means of marine renewable energy. Motivated by economic and environmental aspects, this paper addresses the value proposition and investigates the feasibility of implementing combined wave and solar systems for power supplying offshore oil and gas platforms. Three locations where relevant offshore petroleum activities are currently ongoing were selected as case studies and a reference oil and gas platform was assumed. At each case study location, four wave energy converters and one photovoltaic technology were analysed for three scenarios: wave power only, solar power only and both resources combined. The methodology applied, generalizable to other regions with petroleum activities and relevant wave and solar energy resources, consists in scaling the wave energy converters to match wave climate at site, maximizing their energy production, followed by an economic feasibility analysis. Results show that for all sites the combination of both renewable resources increases electricity production, reduces the intra-annual variability of energy production and intermittency issues, increases capacity factors up to 24% and consequently avoids overdesign. The obtained levelized cost of energy is in the range 131–263 €/MWh and the reduction in emissions was estimated at circa 281, 915 ton/year at each site, which demonstrates the feasibility and interest of providing electricity from these combined systems to offshore oil and gas platforms. The proposed solution provides benefits that could lead to further decreases in the levelized cost of energy, enabling the entrance to new markets for both wave and solar energy, while facilitating the transition to a more sustainable energy mix. Hence, the further technology development is advocated.